Perbandingan Kebijakan Ekonomi Syariah di Negara Negara Islam - Fadhil, Muflihul; Aris, Muhammad; Saputra, Iin; Syahrial, Murah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Islamic economics comes as a new hope in various parties, especially Muslims, Islamic economic growth has been widely used in many parts of the world by using sharia-based economic systems in their policies, by understanding the comparison of Islamic economic policies in Islamic countries, we can evaluate the successes and challenges faced in developing the Islamic financial sector. This is important for formulating more effective strategies to increase financial inclusion, promote sustainable economic growth, and improve people's welfare in Islamic countries. In comparing the Islamic economic policies in several ASEAN, European, and OIC countries, each country has a different approach according to its internal and external conditions. Malaysia and Indonesia are leading the development of Islamic economics with strong regulations and mature financial infrastructure. Meanwhile, European countries such as the UK and Turkey are showing rapid development in this sector although it is still in the early stages of development. On the other hand, OIC countries such as Saudi Arabia and Pakistan show the dominance of Islamic banks and rapid economic growth. The method used in this research is descriptive analysis, a method of collecting data by browsing files, internet websites, documents and information related to the object of research. This research describes how the comparison of Islamic economic policies in Islamic countries.